Lymphoproliferative neoplasms and renal cell carcinoma of clear cell type - where is the link? - Cvetković Zorica; Suvajdžić-Vuković Nada; Cvetković Bora (Vojnosanitetski Pregled)
Introduction. The etiology of higher than expected occurrence of lymphoproliferative neoplasms (LPN) and renal cell carcinoma (RCC) in the same patient has not yet been clarified. Several explanations for this co-occurrence have been postulated: prior cytotoxic treatment, viral infections, immunomodulatory effects of tumor itself and shared genetic and/or environmental factors. Case report. Medical records of 680 consecutive patients with LPN and 570 consecutive patients with RCC diagnosed between January 1997 and December 2011 in two centers were retrospectively analyzed. Co-occurrence of both diseases was registered in five of the patients (3 males, 2 females) and their demographic, clinical and pathological characteristics were presented. Conclusion. Synchronous occurrence of LPN neoplasms and RCC or a short latent period between the diagnoses of these two malignancies in the same patient, as well as the lack of cytotoxic treatment for firstly occurring neoplasm implies a possible common pathobiology of both diseases.